CHALLENGES AND ISSUES OF STARTUP FIRMS IN MSME SECTOR- A STUDY IN DHARWAD DISTRICT (International Journal of Food and Nutritional Sciences, 2023)
The aim of the study is to identify the issues and challenges of the startup industries under MSME sectors. Besides this the study aims to prepare 10 research questions among 51 people as well as business owners to accomplish this study successfully. In the findings chapter there are the SPSS analysis with the survey of total 51 respondent of person. There are three demographical data as well as seven descriptive data are properly illustrate in this chapter. All of the table and figures are shows the basic idea defined the various aspects basis on the research findings portion. There are also a discussion section which is accumulated some authentic idea as per this research project. At last there is conclusion and recommendation portion where idea of this study is appropriately concluded and also recommended point is implement this study for the further execution purpose.